2018
DOI: 10.1111/gbi.12269
|View full text |Cite
|
Sign up to set email alerts
|

Microbially mediated aluminosilicate formation in acidic anaerobic environments: A cell‐scale chemical perspective

Abstract: Through the use of scanning transmission electron microscopy (STEM) combined with other complementary techniques (SEM, cryo-TEM, HRTEM, and EELS), we have studied the interaction of microorganisms inhabiting deep anoxic waters of acidic pit lakes with dissolved aluminum, silica, sulfate, and ferrous iron. These elements were close to saturation (Al, SiO 2 ) or present at very high concentrations (0.12 m Fe(II), 0.12-0. However, these features could also denote biomineralization by active bacterial cells as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 74 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…There, the phosphate was found to be at higher concentrations in the anaerobic monimolimnion zone in comparison to the aerobic mixolimnion. One could also suggest that a part of microbial community might be associated with clay mineral formation, as Sánchez-España et al (2018) earlier showed in acidic pit lake ecosystem in the Iberyan Pyritic Belt. However, relatively high abundance of iron cycling organisms in Sherlovaya Gora pit lake indicates the possibility of active Fe(II) and Fe(III) compounds turnover in the system.…”
Section: Resultsmentioning
confidence: 64%
“…There, the phosphate was found to be at higher concentrations in the anaerobic monimolimnion zone in comparison to the aerobic mixolimnion. One could also suggest that a part of microbial community might be associated with clay mineral formation, as Sánchez-España et al (2018) earlier showed in acidic pit lake ecosystem in the Iberyan Pyritic Belt. However, relatively high abundance of iron cycling organisms in Sherlovaya Gora pit lake indicates the possibility of active Fe(II) and Fe(III) compounds turnover in the system.…”
Section: Resultsmentioning
confidence: 64%
“…Previous studies using high-resolution scanning/transmission electron microscopy of samples collected from various depths in CM showed cells encrusted with mineral precipitates [82,83]. Extracellular polymeric substances (EPS) containing polysaccharides can sorb metals, providing another mechanism for microbial metal resistance [82].…”
Section: Extracellular Metal Sequestrationmentioning
confidence: 99%
“…Rod-shaped cells showed different degree of Fe coating ( Figure 8C ), whereas filamentous cells had very little and cocci had no mineral precipitates in direct contact with their membranes. Previous studies by Scanning Transmission Electron Microscopy (STEM) and Electron Energy Loss Spectroscopy (EELS) have demonstrated that these Fe-coatings in anaerobic bacterial cells inhabiting deep layers of acidic pit lakes consist in Fe(II)-SO 4 ionic complexes adsorbed on carboxylic groups of the cell membrane ( Sánchez-España et al, 2018 ). These coated bacteria were the only ones, that were preserved after the plasma cleaning procedure and under the vacuum conditions of SEM, showing up as external molds ( Figures 7A,B,E ).…”
Section: Resultsmentioning
confidence: 99%